Influence of the biopreparation «Microfit» on biochemical indices of laboratory animals (Experimental biology, 2017)
The introduction of new drugs into clinical practice is feasible only on condition of a detailed study of their specific pharmacological activity and safety at the stage of experimental (preclinical) studies. Preclinical studies of the safety of the medicinal product are aimed at identifying possible damaging effects on the organism of experimental animals and assessing their safety. The investigations allow to reveal the physiological systems of the organism that are most sensitive to the substances of the tested biological product, and also to assess the tolerability of the application of the studied preparation by laboratory animals. Therefore, the development of new medicines, as well as confirmation of their effectiveness and safety for humans, remains a very urgent task in medicine. This article presents experimental data of preclinical tests of the combined biopreparation «Microfit» intended for prevention and correction of intestinal microflora. The preparation consists of lactic acid bacteria of the genus Lactobacillus, an extract of the poplar of balsamic and adsorbing substances. The purpose of this study was to study the chronic toxicity of the biopreparation «Microfit» on the biochemical indicators of laboratory animals with the course intragastric administration.When studying the chronic toxicity of the biopreparation «Microfit» biochemical and pharmacological methods of research. According to the results of the studies within one month of the introduction of the biopreparation and one month (30 days) after the end of the injection, it was established that the biopreparation «Microfit» with course intragastric administration of white outbred rats at the conventional therapeutic dose (30 mg/kg) and dose, in 10 times higher than the conventional therapeutic dose (300 mg/kg) does not have a toxic effect on the main biochemical indicators. Its harmlessness at course intragastric administration and good tolerability by laboratory animals. The obtained results of studying the chronic toxicity of biochemical indicators allow us to assert the safety of the studied biopreparation «Microfit» with subsequent application in medicine.
Keywords: chronic toxicity, biopreparation, biochemical indices.